Anti-Methicillin-Resistant Staphylococcus aureus (MRSA) of Ethanol Extract of God's Crown (Phaleria macrocarpa) Leaves, Peel, and Fruit Flesh - Hestiyani, Rani Afifah Nur; Handini, Tri Okmawati (Fakultas Kedokteran Universitas Brawijaya, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is a pathogen that becomes the main concern since it is a multidrug-resistant organism and causes high morbidity and mortality. This study aimed to investigate the antibacterial activity of ethanolic extract of Phaleria macrocarpa leaves, peel, and fruit flesh on MRSA. This study was an experimental laboratory study with a post-test only control group design to assess the antibacterial activity of ethanolic extract from leaves, peel, and fruit flesh of Phaleria macrocarpa against MRSA ATCC 43300 and MRSA clinical isolates using a disk diffusion method. Extracts from the leaves, peel, and flesh of Phaleria macrocarpa had potential as an antibacterial agent against MRSA ATCC 43300 at a concentration of 40%, although not yet equivalent to antibiotic control. The ethanol extract of Phaleria macrocarpa peel at a concentration of 30-40% had potential as an antibacterial agent against MRSA clinical isolates, although not yet equivalent to antibiotic control. Further research needs to be performed so that Phaleria macrocarpa extract can be a potential source of subsequent antibacterial development against MRSA.